A survey: the role of the internet of things in the development of education - Ridhab Sami Abd-Ali; Sarah Abbas Radhi; Zaid Ibrahim Rasool (Institute of Advanced Engineering and Science, 2020)
There is a demand to change the contents and activities, and adapt the methods for higher education institutions, especially, universities to let researchers and educational to act more efficiently in a digital context. A well-designed campus, finally combining technology, is basic for developing digital university by facilities for learning, teaching, and research, enhancing the student trials, and supplying the convenient settings. Within digital universities, technology can improve security, reduce costs, and offer devices for faculty, scholars, academics, and students. These advantages give more attention to university processes and evolutions, the experience of researchers, and students. In this research, we have done a study on the Internet of things and what its role in the development of education through the review for a group of previous research. In addition, we have studied the smart class and its components and the difference from the traditional class, and then we have displayed the smart laboratories and its applications. At the end of the research, the great importance of Internet things in universities and its importance to the teacher and the student was concluded by learning faster and developing and improving the educational process.